Alfalfa meal as a protein supplement for finishing swine - Koch, B.A.; Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments involving 144 finishing pigs were conducted to evaluate alfalfa meal in diets of finishing swine. Results indicate that finishing swine can utilize diets with up to 20% alfalfa meal without significantly effecting pig performance. This suggests the maximum crude fiber level that the finishing pig (125 lbs. to market) can tolerate without a significant reduction in daily gain is 6-7% of the diet. Pelleting the diet may extend this level in that we noted a satisfactory rate of gain and feed/gain ratio when 25% alfalfa meal diets (7.4% crude fiber) were fed.
Swine Industry Day 1974 is known as Swine Day, 1974
Keywords: Swine; Alfalfa meal; Protein; Finishing pigs; Crude fiber